Note—More on Planning for Freedom - Singhal, K.; Vyasulu, V. (Management Science, 1978)
The aim of this note is to add objectivity to the article by Van Gigch (Van Gigch, J. P. 1976. Planning for freedom. Management Sci. 22 (9, May).). The main points are that the four models of Van Gigch are historical stages of development, not options at a given point of time; and that the role of the elite is not an impartial one.